Willingness of the Public to Share Geolocation Information in a U.S. Census Bureau Survey. (August 2019) - Olmsted-Hawala, Erica; Nichols, Elizabeth
In 2016, the U.S. Census Bureau conducted a split-panel experiment to explore the public's willingness to share geolocation information within a survey. A sample of participants from a nonprobability panel were invited to take part in an online survey using their mobile device. Within the survey, one question asked for their address and then the survey requested permission to access their geolocation information. Depending on the study condition, the survey varied how the geolocation request was made and where in the survey the address and geolocation requests appeared. Results showed that the treatment that explicitly asked for permission in addition to the device's default permission request increased female respondents' sharing of that data but not male respondents' sharing. Results also showed that placing the address and geolocation request toward the end of the survey significantly increased the willingness of all respondents to share their location information. Results indicated that respondents with more education and nonminority respondents were more willing to share their location data, but willingness to share location data did not depend on age of the respondent. Assuming that the respondents reported truthfully that they were at home while taking the survey and entered their home address, we found the geolocation data to be accurate to the correct block a little more than 50% of the time.